The international implications of national and local coordination on building energy codes: Case studies in six cities. (1st August 2018) - Evans, Meredydd; Yu, Sha; Staniszewski, Aaron; Jin, Luting; Denysenko, Artur
Abstract: Building energy efficiency is an important strategy for reducing greenhouse gas emissions globally. In fact, 55 countries have included building energy efficiency in their Nationally Determined Contributions (NDCs) under the Paris Agreement. This research uses building energy code implementation in six cities across different continents as case studies to assess what it may take for countries to implement the ambitions of their energy efficiency goals. Specifically, we look at the cases of Bogota, Colombia; Da Nang, Vietnam; Eskisehir, Turkey; Mexico City, Mexico; Rajkot, India; and Tshwane, South Africa, all of which are "deep dive" cities under the Sustainable Energy for All's Building Efficiency Accelerator. The research focuses on understanding the baseline with existing gaps in implementation and coordination. The methodology used a combination of surveys on code status and interviews with stakeholders at the local and national level, as well as review of published documents. We looked at code development, implementation, and evaluation. The cities are all working to improve implementation, however, the challenges they currently face include gaps in resources, capacity, tools, and institutions to check for compliance. Better coordination between national and local governments could help improve implementation, but that coordination is not yet well established. For example, all six of the cities reported that there was little to no involvement of local stakeholders in development of the national code; only one city reported that it had access to national funding to support code implementation. More robust coordination could better link cities with capacity building and funding for compliance, and ensure that the code reflects local priorities. Understanding gaps in implementation can also help in designing more targeted interventions to scale up energy savings. Graphical abstract: Image 1 Highlights: Fifty-five countries include building energy efficiency in their NDCs under the Paris Agreement. Six cities were used as case studies to assess what it may take for countries to reach their energy efficiency targets. Gaps in coordination between national and local governments are creating challenges in implementation. Understanding the feasibility of various interventions helps in designing effective policies for large-scale change.